Low-dose aspirin for prevention of pre-eclampsia and its complications: a cost-effectiveness analysis. (16th November 2010) - Vogel, SA; Rajaii, R; Ottaviano, G; Kim, L; Yeaton-Massey, A; Caughey, AB
Abstract : Objective: The authors investigated whether low-dose aspirin (ASA) is a cost-effective means of reducing the risk of pre-eclampsia. Study Design: A decision analytic model was designed comparing ASA prophylaxis vs no prophylaxis in a theoretical cohort of 100 000 pregnant women. Costs and prevalences were derived from existing randomised controlled trails. Utilities were applied to discounted life expectancy to generate quality-adjusted life years (QALYs), which were discounted at 3%. A cost-effectiveness threshold of $100 000/QALY was utilised. Results: ASA prophylaxis is the dominant strategy. It is both cheaper ($18 720 vs $18 804) and marginally more effective (26.7417 QALYs vs 26.7422 QALYs). Additionally, negative outcomes associated with pre-eclampsia were reduced in the intervention group, most notably fewer preterm births (10 312 vs 10 251). In sensitivity analysis, when the authors varied the efficacy of ASA prophylaxis, it remained cost-effective up to a relative risk of 0.91 for all nulliparous women and 0.98 for women with a 25% risk of pre-eclampsia. Conclusion: Low-dose ASA appears to be a cost-effective prophylaxis for pre-eclampsia over a wide range of assumptions, particularly for women at elevated risk for pre-eclampsia. Abstract PM.42 Outcomes for 100, 000 Nulliparous Pregnant Women NO ASA ASA Preeclampsia 5000 4150 Preterm Births 103120 10250.5 Neonatal Death 257.1 256.9 Maternal Deaths 13.8 13.1 Neurodevelopmental Disability 370.9 369.7 Costs 51, 880, 421, 000 51, 871, 989, 000 QALYs 2674174.1 2674224.